Association between endometriosis and gut microbiota: systematic review and meta-analysis - Yuanyue, Li; Dimei, Ouyang; Ling, Liu; Dongyan, Ren; Xiaomei, Wu (Frontiers in Microbiology, 2025)
BackgroundEndometriosis, a complex gynecological disorder, has been increasingly linked to gut microbiota dysbiosis, suggesting its potential role in disease pathogenesis.MethodsThis systematic review and meta-analysis explore the association between gut microbiota and endometriosis by evaluating alpha and beta diversity measures across 11 studies involving 1,727 women, including 433 diagnosed with endometriosis and 1,294 controls. Statistical analysis was performed utilizing either random effects models or fixed models by Revmen5.2 and STATA softwares.ResultsSignificant differences in alpha diversity between endometriosis and control groups were observed using the Shannon Index (SMD = 0.39; p < 0.00001), Subgroup analysis showed significant differences for Chinese (SMD = 0.48; 95% CI = 0.14 to 0.82; p = 0.006; I2 = 30%), Swedish, (SMD = 0.55; 95% CI = 0.27 to 0.83; p = 0.0001; I2 = 30%) and Spanish (SMD = 0.34; 95% CI = −0.02 to 0.85; p < 0.06; I2 = 27%), compared to others which highlighting the correlation between gut microbiota diversity and endometriosis across different demographic groups. The Simpson Index also revealed a notable difference in richness (SMD = 0.91; p = 0.03). However, no significant differences were detected using the Chao Index (SMD = 0.37; p = 0.11). These findings underscore the importance of diversity measures in understanding gut microbiota’s role in endometriosis. Seven studies employed PCoA, two used the Bray–Curtis dissimilarity index, and one performed PCA, revealing notable dissimilarities in gut microbiota composition between the groups. Using the Newcastle-Ottawa Scale, most studies scored ≥7 stars, indicating high quality. The funnel plot and Egger’s linear regression analysis indicated no publication bias.ConclusionThis study highlights significant alterations in gut microbiota diversity and composition in women with endometriosis, emphasizing the potential role of gut microbiota in its pathogenesis. Future research should focus on standardizing reporting methods to facilitate deeper quantitative analyses.Systematic Review RegistrationPROSPERO (registration number RD42024611701).